The eukaryotic tRNA-guanine transglycosylase enzyme inserts queuine into tRNA via a sequential bi?bi mechanism - Southern, John; Kelly, Vincent; Connon, Stephen (My University, 2020)
Eukaryotic tRNA-guanine transglycosylase (TGT) – an enzyme recently recognised to be of potential therapeutic importance – catalyses base-exchange of guanine for queuine at the wobble position of tRNAs associated with 4 amino acids via a distinct mechanism to that reported for its eubacterial homologue. The presence of queuine is unequivocally required as a trigger for reaction between the enzyme and tRNA and exhibits cooperativity not seen using guanine as a substrate.
PUBLISHED
Keywords: Eukaryotic tRNA-guanine transglycosylase (TGT); queuine; eubacterial homologue